Odpowiedź :
Odpowiedź:
a) a₁=5 a₂=8 a₃=11 a₄=14
r= a₂-a₁= 8-5=3
to ciag arytmetyczny
aₙ= a₁+(n-1)*r= 5+ (n-1)*3 = 5+3n-3
aₙ= 3n+2
b)
r= 10-14= -4
aₙ= 14+(n-1)*(-4)= 14-4n+4
aₙ=-4n +18
Szczegółowe wyjaśnienie:
[tex]a) \\\\a_1=5\\a_2=8\\a_3=11\\a_4=14\\\\a_2=a_1+r\\8=5+r /-5\\3=r\\\\a_3=a_2+r\\11=8+3\\\\a_4=a_3+r\\14=11+3\\\\a_n=5+(n-1)*3\\a_n=5+3n-3\\a_n=2+3n[/tex]
[tex]b) \\\\a_1=14\\a_2=10\\a_3=6\\a_4=2\\\\a_1+r=a_2\\14+r=10 /-14\\r=-4\\10-4=6\\\\6-4=2\\\\a_n=14+(n-1)*(-4)\\a_n=14-4n-4\\a_n=10-4n[/tex]